A selective and economic carbon catalyst from waste for aqueous conversion of fructose into 5-hydroxymethylfurfural. Issue 36 (23rd March 2016) - Deng, Tiansheng; Li, Jiangong; Yang, Qiqi; Yang, Yongxing; Lv, Guangqiang; Yao, Ying; Qin, Limin; Zhao, Xianlong; Cui, Xiaojing; Hou, Xianglin
Abstract : A selective aqueous conversion of fructose to HMF using carbon catalysts from pulping waste sodium ligninsulfonate. Abstract : It is of vital importance to design stable and selective heterocatalysts for aqueous production of platforms from biomass-derived sugars. This paper describes a selective aqueous conversion of fructose to HMF using carbon catalysts from pulping waste sodium ligninsulfonate (SLS). The effect of carbonization atmospheres (N2 flow, static air and air flow) on the structure, porosity, compositions and acidic properties of carbon catalysts were investigated by thermogravimetry-mass spectrum analysis, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, Boehm titrations, N2 adsorption–desorption isotherms and elemental analysis. The carbonization in air flow favored the formation of more oxygen-containing functional groups and micropores, while more sulfonic groups and meso-/macro-pores were formed during carbonization in a static air atmosphere. Both oxygen- and sulfur-containing groups were acid sites, and their total amount was the largest when carbonized in air flow, followed by static air and N2 flow. The positive correlation between the acid amounts and fructose conversion of carbon catalysts clearly demonstrated the catalytic effect of the acid sites. The steric hindrance of micropores in carbon catalysts restricted the formation of humins and promoted the HMF selectivity compared with meso-/macro-pores.